2021
DOI: 10.13057/biodiv/d221256
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of sponge-associated fungi from a mangrove forest in Kemujan Island, Karimunjawa National Park, Indonesia

Abstract: Abstract. Sibero MT, Pribadi R, Larasati SJH, Calabon MS, Sabdono A, Subagiyo S, Frederick EH. 2021. Diversity of sponge-associated fungi from a mangrove forest in Kemujan Island, Karimunjawa National Park, Indonesia. Biodiversitas 22: 5695-5605. Plenty of studies have reported interesting biological properties and bioactive compounds from sponge-associated fungi in Indonesia. However, only a few studies consider their biodiversity. Most of the studies collected the sponge from the coral reef ecosystem and bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…These orders have been found in different sponges around the world and might occupy important functions in the sponge holobiont (Yu et al, 2013;He et al, 2014;Bovio et al, 2019;Karthik and Li, 2019). The genera Aspergillus and Penicillium have often been recovered from marine sponges and macroalgae (Venkatachalam et al, 2015;Yang et al, 2018;Moreno-Pino et al, 2020;Sibero et al, 2021) and our study reports Aspergillus in the sponge Biemna sp. and that of Penicillium in the brown algae Turbinaria conoides.…”
Section: Discussionsupporting
confidence: 61%
“…These orders have been found in different sponges around the world and might occupy important functions in the sponge holobiont (Yu et al, 2013;He et al, 2014;Bovio et al, 2019;Karthik and Li, 2019). The genera Aspergillus and Penicillium have often been recovered from marine sponges and macroalgae (Venkatachalam et al, 2015;Yang et al, 2018;Moreno-Pino et al, 2020;Sibero et al, 2021) and our study reports Aspergillus in the sponge Biemna sp. and that of Penicillium in the brown algae Turbinaria conoides.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, Buzzini et al (2017) reported their marine yeasts were classified as facultative marine fungi as well. Marine fungi are suggested to be carried from the terrestrial to the ocean through the biological vector, rain, wind or other natural phenomenon (Sibero et al 2021). They are also equipped with special mechanism to tolerate the environmental conditions, such as morphology regulation, cell anatomy, cation transport entity modulation, and secondary metabolite production (Hohmann 2002;Ariño et al 2010;Nagano et al 2010;Sharma and Sharma 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Species of marine fungi reported in 2021–2022 were Aspergillus spp. [ 115 , 133 ], Aspergillus flavus [ 122 ] , Aspergillus fumigatus [ 122 ], Aspergillus ochraceus, Aspergillus niger , Aspergillus nomius [ 116 ], Aspergillus aculeatus [ 118 ], Penicillium spp. [ 122 , 126 ], Penicillium citrinum [ 118 ], Penicillium oligosporum [ 125 ], Diaporthe stewartii [ 118 ], Diaporthe spp.…”
Section: Indonesian Marine Macro Organismsmentioning
confidence: 99%